2018
DOI: 10.1007/s00402-018-3056-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent postoperative step-off of the posterior malleolus leads to higher incidence of post-traumatic osteoarthritis in trimalleolar fractures

Abstract: Background Traditionally, size of the posterior fragment is considered the most important indicator for fixation in trimalleolar fractures. It remains unclear which factors contribute to worse functional and radiological outcome. This study was designed to determine predictors for the development of posttraumatic osteoarthritis and worse functional outcome in trimalleolar fractures. Methods This retrospective cohort study evaluated outcomes of 169 patients with a trimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 34 publications
(58 reference statements)
0
53
1
3
Order By: Relevance
“…Failure to restore congruity of the articular surface within 2 mm, including the posterior malleolus, is associated with worse functional outcomes at 1 year compared with patients whose congruity is restored. 1,33 A significant incidence of radiographic arthritis occurs with step-offs of >2 mm at the posterior malleolus, regardless of fragment size. 3 Congruity with stability and degree of reduction may be important prognostic factors, along with joint surface involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to restore congruity of the articular surface within 2 mm, including the posterior malleolus, is associated with worse functional outcomes at 1 year compared with patients whose congruity is restored. 1,33 A significant incidence of radiographic arthritis occurs with step-offs of >2 mm at the posterior malleolus, regardless of fragment size. 3 Congruity with stability and degree of reduction may be important prognostic factors, along with joint surface involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Langenhuijsen et al [7] emphasized the importance of the quality of the posterior malleolus reduction, and advocated that the joint congruity, not the fragment size, is the main factor determining the need for fracture fixation. Verhage et al [29] suggested to correct intra-articular step-off of intraarticular posterior malleolar fragments to reduce the risk of developing osteoarthritis. Tosun et al [30] showed that the fixation of PMF is closely related to the successful radiological and functional outcomes of trimalleolar fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that clinical outcome is related to fracture displacement, articular surface congruency, and residual tibiotalar subluxation, rather than PMF size. 39 , 45 , 48 Several studies, 11 , 53 , 56 including a review from 2018 by Verhage et al, 52 argue that postoperative step-off is the most important factor predicting posttraumatic osteoarthritis. The current study showed a surprising trend toward more osteoarthritis in group A ( P = .06).…”
Section: Discussionmentioning
confidence: 99%